Analysis of the use, effectiveness, and efficiency of the pick and roll in elite women’s basketball - Amatria, M.; Iván-Baragaño, I.; Losada, J. L.; Maneiro, R. (Frontiers in Sports and Active Living, 2025)
This study investigates the effectiveness and outcomes of “pick and roll” plays in elite women's basketball, focusing on the 2021-2022 EuroLeague Final Four. The main objective is to analyze the tactical efficiency of these actions and identify the most effective resolution strategies. A total of 298 plays from 1,757 events across four matches were examined using an observational methodology, adhering to a Nomothetic, Point, and Multidimensional (N/P/M) design. An observational instrument consisted on twenty-three criteria and 126 categories was developed to codify the actions, with reliability confirmed by a Cohen's Kappa value of 0.93, indicating “almost perfect” agreement. Results show that 71.8% of “pick and roll” plays concluded with a shot, with the highest success rates achieved when the screener executed the final attempt near the basket. Actions with fewer passes post-screen were significantly more effective, and collective strategies, such as passing to the screener, outperformed individual efforts by the ball handler. In addition, the multivariate results highlight the second and third quarters of the game as the most important when it comes to executing an effective offensive pick & roll. These findings emphasize the importance of immediate actions post-screen, tactical fluidity, and proximity to the basket, providing valuable insights to enhance offensive strategies in competitive women's basketball.